The SGN VIGS Tool: User-Friendly Software to Design Virus-Induced Gene Silencing (VIGS) Constructs for Functional Genomics - Fernandez-Pozo, Noe (2015)
Virus-induced gene silencing (VIGS) is a powerful method to study gene function in plants. It is based on plant defense mechanisms against viral gene replication and allows high-throughput silencing of genes of interest. However, it can also elicit suppression of off-target genes with sequence similarity, confounding the observed phenotype. Although VIGS is widely used in plant research, no tool is currently available for the design of constructs specifically for this technique. Therefore, at the Sol Genomics Network (SGN) we have developed the SGN VIGS tool to assist researchers with the selection of appropriate regions for silencing experiments (http://solgenomics.net/tools/vigs). This web tool was developed using Perl, JavaScript, AJAX and HTML5 canvas to allow a fast and interactive graphical representation of the results, based on target and off-target positions and integrating the results with gene expression data.